Investigation of latch-up behaviour in 0.5 micron CMOS technology / Wan Fazlida Hanim Abdullah, Suhana Sulaiman and Mohd Jamil Napiah - Abdullah, Wan Fazlida Hanim; Sulaiman, Suhana Sulaiman; Napiah, Mohd Jamil (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2005)
The research project investigates available latch-up test structures from MIMOS Berhad and covers current-voltage characterization of silicon-controlled rectifier behaviour of parasitic BJTs in CMOS technology. Measurement setup utilizing the structures for IV measurements are designed. A suitable measurement routine for the testing of latch-up in MOS device engineering at wafer level is developed for use in research environment.Tests are done on available MIMOS test structures representing twin tub technology and silicon-on-insulator substrate using automatic semiconductor characterization system comprising of Semiconductor Parametric Characterization Software (SPECS), UFK200 automatic prober and Agilent 4073 tester. Avalanche induced latch-up of three types of device were demonstrated: SOI without thickness adjustment, SOI with thinner layer due to thickness adjustment and bulk silicon control device are demonstrated. Immunity towards latch-up is improved for devices on BSOI substrate.